Different Differences [Diferentes Diferencias] - Bulo-Vargas, V (Universidade Estadual Paulista (UNESP), 2017)
This article presents the idea of “difference” as discussed by some authors linked “difference thinking”. These different differences constitute a drama where each one will be displayed in its irreducibility and its constitutive relationship to the others; some differences will converge with others or simply displace them. Ontological difference, difference, pure difference, the difference of bodies, and colonial difference, show that the problem of difference, when brought into specific areas such as gender, ethnicity, etc., must always be approached from the irreducibly plural nature of difference. © 2017, Universidade Estadual Paulista (UNESP). All rights reserved.